Prediction of Inflorescence Emergence in ‘Yu Her Pau’ Litchi Under Climate Change Using an Optimised Model - JenYu Chang; Lisa Tang; Chu‐Chung Chen; Yi‐Ting Zhang; Chi‐Ling Chen (Food and Energy Security)
ABSTRACT For litchi (Litchi chinensis), successful floral induction requires adequate cool temperatures in winter, perceived by mature leaves like many other subtropical fruit species. As a result, rising ambient temperatures due to global climate change has posed a threat to litchi flowering and fruit production. The goal of this research was to assess the potential impacts of climate change on flowering in ‘Yu Her Pau’ litchi on Taiwan. To better characterise the relationship between temperatures and inflorescence emergence (IE), we built a model by applying the beta‐distribution function method with 12 phenological datasets (two orchard blocks for 6 years) recorded from field‐grown ‘Yu Her Pau’ litchi trees. For this predictive model, the minimum, maximum, and optimal temperatures that resulted in successful floral induction were estimated to be 0.0°C, 21.9°C, and 19.8°C, respectively; under these criteria, at least 60.37 units of cumulative cool temperatures are necessary for IE based on the historical data. Subsequently, the IE model was used to evaluate the likelihood of successful flowering in ‘Yu Her Pau’ litchi at four major producing areas on Taiwan during five decades from 2026 to 2075, respectively, under three separate climate change (emission) scenarios based on three General Circulation Models (GCMs) in. Our results, based on any of the GCMs, suggested that ‘Yu Her Pau’ litchi grown on Southern Taiwan could face poor flowering due to insufficient cool winter temperatures in the coming decade even in the emission scenario with very stringent mitigation effort, which can lead to serious crop loss in the near future.